Feeding behavior of Aphis glycines (Hemiptera: Aphididae) on soybeans exhibiting antibiosis, antixenosis, and tolerance resistance - Baldin, Edson L. L. [UNESP]; Stamm, Mitchell D.; Bentivenha, Jose P. F.; Koch, Kyle G.; Heng-Moss, Tiffany M.; Hunt, Thomas E. (Florida Entomological Soc, 2018)
Aphis glycines Matsumura (Hemiptera: Aphididae) is a serious pest of soybean in North America. Plant resistance is a valuable tool for the management of this pest, and a better understanding of the interactions between aphid and soybeans expressing varying levels and different categories of resistance can assist in the development of aphid resistant or tolerant genotypes. The electrical penetration graph (EPG) technique was used to evaluate the feeding behavior of A. glycines (biotype 1) on 4 soybean genotypes: (1) 'Dowling' (contains Rag1 gene and exhibits antibiosis); (2) PI 200538 (contains Rag2 gene and exhibits antixenosis); (3) KS4202 (exhibits tolerance); and (4) 'D76RR' (susceptible to aphid). Aphids spent shorter periods in the sieve element phase on 'Dowling' and exhibited a greater number of pathway phases, non-probing events, and a longer time in non-probing events in PI 200538 and 'Dowling.' For 'SD76RR' and KS4202, aphids demonstrated more sustained phloem ingestion, spent shorter time in non-probing events, and exhibited fewer pathway phases and potential drops. These results indicate that resistance factors are present in the phloem of 'Dowling.' For PI 200538, it is suggested that antixenotic factors are involved in resistance to A. glycines. Because KS4202 is tolerant to biotype 1 of A. glycines, the suitability of this genotype was expected already. This study provides important data that contribute to the understanding of how soybean aphids (biotype 1) feed on soybean genotypes with various aphid resistant genes and categories. In addition to assisting in the distinction between resistance categories, these results are useful in soybean breeding programs focusing on developing genotypes with greater resistance to insects.
Keywords: host plant resistance; electrical penetration graph; soybean aphid